2022
DOI: 10.1089/ten.tea.2021.0167
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Neonatal, Juvenile, and Adult Donors on Rejuvenated Neocartilage Functional Properties

Abstract: Cartilage does not naturally heal, and cartilage lesions from trauma and wear-and-tear can lead to eventual osteoarthritis. To address long-term repair, tissue engineering of functional biologic implants to treat cartilage lesions is desirable, but the development of such implants is hindered by several limitations including 1) donor tissue scarcity due to the presence of diseased tissues in joints, 2) dedifferentiation of chondrocytes during expansion, and 3) differences in functional output of cells dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Several studies have reported reduced collagen synthesis in 3D cultures with donor age using agarose hydrogels and hydrolytically degradable poly­(ethylene glycol) hydrogels . On the contrary, a scaffold-free self-assembly process for 3D regeneration of cartilage reported similar biochemical contents regardless of donor age . These studies demonstrate that chondrocyte bioactivity differs with age of the donor but the extent may depend on the signaling factors (e.g., growth factors) and the culture environment.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Several studies have reported reduced collagen synthesis in 3D cultures with donor age using agarose hydrogels and hydrolytically degradable poly­(ethylene glycol) hydrogels . On the contrary, a scaffold-free self-assembly process for 3D regeneration of cartilage reported similar biochemical contents regardless of donor age . These studies demonstrate that chondrocyte bioactivity differs with age of the donor but the extent may depend on the signaling factors (e.g., growth factors) and the culture environment.…”
Section: Introductionmentioning
confidence: 81%
“…13 On the contrary, a scaffold-free self-assembly process for 3D regeneration of cartilage reported similar biochemical contents regardless of donor age. 14 These studies demonstrate that chondrocyte bioactivity differs with age of the donor but the extent may depend on the signaling factors (e.g., growth factors) and the culture environment. Taken together, a successful cartilage tissue engineering strategy must consider the impact of donor variations.…”
Section: Introductionmentioning
confidence: 83%
“…Specifically, cells were isolated from six juvenile minipig donors (5-7 months old, three male, three female) and expanded to generate MCBs derived from each donor. We estimate that the juvenile cells used in this study correspond to approximately 10-12 years of age in the human [21]. It has been reported that in the human, chondrocytes isolated from donors under 13 years of age had greater proteoglycan production and collagen type II and type IX gene expression than adult donors [22].…”
Section: Structure Of the Acp Cell Bankmentioning
confidence: 97%
“…Recent in vitro studies have shown the similar mechanical and biochemical attributes of rib cartilage and articular cartilage, deeming costal cartilage a valuable cell source for articular cartilage tissue engineering [ 15 ]. Additionally, self-assembled neocartilages have recently been made from extensively passaged, rejuvenated costal chondrocytes [ 16 , 17 ], allowing for thousands of robust neocartilage implants to be made from one rib cartilage biopsy [ 18 ]. Self-assembled neocartilage implants made with costal chondrocytes have also been used to treat cartilage defects in Yucatan minipig models [ 19 ].…”
Section: Introductionmentioning
confidence: 99%